Development of Entada Mannii Fiber Polypropylene Matrix Composites for Light Weight Applications - O.P. Balogun; J.A. Omotoyinbo; K.K. Alaneme; P.A. Olubambi (Tribology in Industry, 2017)
This study investigates the use of Entada mannii fiber as potential reinforcement of thermoplastic composites suitable for light weight applications. Composites of 5 wt.%, 10 wt.% and 15 wt.% were produced by compression moulding with 5 wt.% Maleic anhydride polypropylene (MAAP) as compatibilizers. Tensile properties, impact strength and hardness properties of the composites were evaluated. Thermogravimetric analysis (TGA), X-ray diffractograms (XRD) and Fourier transformed infrared spectroscopy (FTIR) of treated and untreated fibers were evaluated while the fractographic analysis of surface morphology of the composites was performed using Scanning electron microscopy. The result revealed that reinforcing thermoplastic with 15 %.wt treated Entada mannii fiber revealed a greater improvement in tensile strength and Young's modulus by 58 % and 61 % respectively relative to pure PP and the hardness properties of the composite also increased by 56 % as compared with pure PP . This improvement is noticeable for the 15 wt.% treated fiber reinforced composites and could be attributed to good interfacial bonding between the fiber and the matrix. However impact strength of treated fiber composite revealed an improvement with 10 wt.% treated fiber composites by 48 % relative to Pure PP. Fracture surface images of treated fiber reinforced composites revealed less fiber pullout while the TGA showed the treated fiber degrades at higher temperature as compared with untreated fiber. Thus, the cellulose percentage crystallinity index of the treated fiber increases from 47.9 % to 57 % as a result of the influence of alkaline treatment.